Time to Develop and Predictors for Incidence of Tuberculosis among Children Receiving Antiretroviral Therapy - Fassikaw Kebede (Hindawi Limited, 2021)
Infection by the human immune deficiency virus (HIV) is the strongest risk factor for latent or new infection of tuberculosis (TB) through reduction of CD4 T-lymphocytes and cellular immune function. Almost one-third of deaths among people living with HIV are attributed to tuberculosis. Despite this evidence, in Ethiopia, there is a scarcity of information regarding the incidence of tuberculosis for children living with HIV. Thus, this study assessed time to develop and predictors for incidence of tuberculosis in children attending HIV/AIDS care in public hospitals: North West Ethiopia 2021. Methods. A facility-based retrospective cohort study was conducted among 421 seropositive children on antiretroviral therapy in two hospitals between January 1, 2011 and December 31, 2020. EPI-DATA version 3.2 and STATA/14 software were used for data entry and analysis, respectively. Tuberculosis-free survival time was estimated using the Kaplan-Meier survival curve. Bivariate and multivariable Cox regression model was fitted to identify predictors at a P value <0.05 within 95% CI. Results. In the final analysis, a total of 421 seropositive children were included, of whom, 64 (15.2%) developed tuberculosis at the time of follow-up. The mean (±SD) age of the children was 10.62±3.32 years, with a median (IQR) time to develop TB that was 23.5 (IQR=±19) months. This study found that the incidence of tuberculosis was 5.9 (95% CI: 4.7; 7.6) per 100 person-years (PY) risk of observation. Cases at baseline not taking cotrimoxazol preventive therapy (CPT) (AHR=2.5; 95% CI, 1.4-4.7, P<0.021), being severely stunted (AHR=2.9: 95% CI, 1.2-7.8, P<0.03), and having low hemoglobin level (AHR=4.0; 95% CI, 2.1-8.1, P<0.001) were found to be predictors of tuberculosis. Conclusion. A higher rate of tuberculosis incidence was reported in our study as compared with previous studies in Ethiopia. Cases at baseline not taking cotrimoxazol preventive therapy (CPT), being severely stunted, and having low hemoglobin (≤10 mg/dl) levels were found to be at higher risk to developed TB incidence.